2004
DOI: 10.1063/1.1737807
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of an all-plastic WO3⋅H2O-based infrared modulator

Abstract: Articles you may be interested inInfrared-to-visible upconversion emission in Er3+ doped TeO2-WO3-Bi2O3 glasses with silver nanoparticles J. Appl. Phys. 112, 063519 (2012); 10.1063/1.4754468 Demonstration of enhanced population feeding of the 1.53 μ m emitting level of Er 3 + in Te O 2 -W O 3 -Li 2 O -P 2 O 5 glasses using upconversion luminescence spectroscopy Flexible electrochromic reflectance device based on tungsten oxide for infrared emissivity control WO 3 •H 2 O powder embedded in a plastic matrix has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The attention in studying the electrical properties of tungsten trioxide monohydrate WO 3 ·H 2 O was stimulated by its promise as regards use as a basic compound in infrared emissivity/reflectivity flexible modulators driven by the electrochemical insertion of lithium ions. The injection of electrons comes with the insertion of these cations in the compound. Hence, the variation in electron population can induce the simultaneous changes in optical and electrical behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The attention in studying the electrical properties of tungsten trioxide monohydrate WO 3 ·H 2 O was stimulated by its promise as regards use as a basic compound in infrared emissivity/reflectivity flexible modulators driven by the electrochemical insertion of lithium ions. The injection of electrons comes with the insertion of these cations in the compound. Hence, the variation in electron population can induce the simultaneous changes in optical and electrical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A previous paper has shown that WO 3 ·H 2 O powder embedded in a plastic matrix could be used as the active component in the LiCoO 2 /Li electrolyte/WO 3 ·H 2 O system. With Li + intercalation the optical behavior has been well described by a Drude−Lorentz model which is often correlated to the existence of free electrons and/or to a high electronic conductivity . The role of the WO 3 ·H 2 O powder morphology was investigated on two types of compounds obtained by two different elaboration methods, ,, the first one being constituted by microparticles (Figure a) and the second by nanoparticles (Figure b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the flexible devices could adjust to components with complex shapes, and their low weight would result in energy saving, especially for satellites. We recently reported the realization of a flexible emissivity modulator based on WO 3 ·H 2 O driven by the electrochemical insertion of lithium. The injection of electrons comes with the insertion of small cations (typically H + or Li + ) in the compound. Hence, the variation in electron population can induce the change in optical behavior.…”
Section: Introductionmentioning
confidence: 99%